Determining the Level of Service Scale of Public Transport System considering the Distribution of Service Quality - Min Wang; Baohua Mao; Yanqiang Yang; Ruijia Shi; Junsheng Huang (Journal of Advanced Transportation)
In China, many cities are building themselves the transit metropolis, and the reasonable evaluation of level of service (LOS) of public transport system (PTS) is one important aspect. However, to determine the overall LOS is hard because the distribution of service in PTS is not homogeneous with regard to time and space. To address this problem, this study proposes a general framework to determine the LOS scale of PTS based on the distribution of service quality. Under the framework, two classification methods are discussed. Method 1 uses two parameters, the mean and coefficient of variation to model the distribution, and Method 2 is an existing approach that only considers mean. Then the specific use of the framework is expounded for the service attribute of crowding, and Beijing subway line LOS is evaluated. The line LOS is divided into I–IV, whose threshold is expressed as a function of mean and coefficient of variation. The results show that 57.8% of the sample points are in the most crowding level IV in morning peak hours by Method 1, but 60.9% of sample points are in a comfortable level II by Method 2, and the former is more consistent with reality. In addition, it reveals which lines and time periods need to improve the service level. The research proves the feasibility of considering the service distribution to determine the overall LOS of PTS, and it is useful for capturing more detailed information of the system performance in time and space. This research can provide an approach for evaluating and helping to improve the overall service level of PTS for public transport authorities.